When fathers are instant losers: homogenization of rDNA loci in recently formed Cardamine × schulzii trigenomic allopolyploid - Zozomová-Lihová, Judita; Mandáková, Terezie; Kovaříková, Alena; Mühlhausen, Andreas; Mummenhoff, Klaus; Lysak, Martin A; Kovařík, Aleš (The New phytologist, 2014)
Recently formed allopolyploids represent an excellent system to study the impacts of hybridization and genomic duplication on genome structure and evolution. Here we explored the 35SrRNA genes (rDNA) in the Cardamine × schulzii allohexaploid that was formed by two subsequent hybridization events within the past c. 150 yr. The rDNA loci were analyzed by cloning, next generation sequencing (NGS), RT-PCR and FISH methods. The primary C. × insueta triploid hybrid derived from C. rivularis (♀) and C. amara (♂) had gene ratios highly skewed towards maternal sequences. Similarly, C. × schulzii, originating from the secondary hybridization event involving C. × insueta (♀) and C. pratensis (♂), showed a reduction in paternal rDNA homeologs despite an excess of chromosomes inherited from C. pratensis. We also identified novel rDNA loci in C. × schulzii, suggesting that lost loci might be slowly reinstalled by translocation (but not recombination) of genes from partner genomes. Prevalent clonal propagation of allopolyploids, C. × insueta and C. × schulzii, indicates that concerted evolution of rDNA may occur in the absence of extensive meiotic cycles. Adoption of NGS in rDNA variant analysis is highly informative for deciphering the evolutionary histories of allopolyploid species with ongoing homogenization processes.
Keywords: mezerníky ribozomální DNA; Cardamine; sekvence nukleotidů; druhová specificita; Crosses, Genetic; DNA, Ribosomal; Phylogeny; Chromosomes, Plant; genetické lokusy; klonování DNA; concerted evolution; regulace genové exprese u rostlin; Brassicaceae; Gene Expression Regulation, Plant; Genome, Plant; křížení genetické; genetická variace; Genetic Variation; rDNA; hybrids; Base Sequence; fylogeneze; Species Specificity; vysoce účinné nukleotidové sekvenování; ribozomální DNA; High-Throughput Nucleotide Sequencing; hybridization; chromozomy rostlin; Cloning, Molecular; polyploidie; DNA, Ribosomal Spacer; Polyploidy; genom rostlinný; Genetic Loci; polyploidy